The COVID-19 pandemic and the intention of cash waqf: Approach to theory of reason action, level of religiosity and trust in institutions - Juliana Juliana; Muhammad Jihan; Rida Rosida; Shafinar Ismail; Mumuh Muhammad; Tony Seno Aji (al-Uqud : Journal of Islamic Economics, 2023)
This study aims to see the intention of cash waqf in the Muslim community in Bandung Raya during the Covid-19 Pandemic and to see how the influence of Theory of Reasoned Action (TRA), namely subjective attitudes and norms with an additional level of religiosity and trust in institutions. The method used in this study is a quantitative approach with a causal descriptive design. The analytical tool used is Partial Least Square-Structural Equation Modeling (PLS-SEM) with the SmartPLS v application. 3.2.9. The subject of this study is the Muslim community in Bandung Raya with a total sample of 210 respondents. The results showed that attitudes, subjective norms, levels of religiosity and trust in institutions were in the high category. There are four variables that have a significant positive effect on the intention of the Muslim community in Bandung Raya to donate money during the Covid-19 pandemic, namely attitudes, subjective norms, level of religiosity and trust in institutions. The results of this study also confirm that attitudes, subjective norms, religiosity and trust are very important in Encouraging the intention to donate during the Covid-19 pandemic.